Benign glial cysts of the pineal gland: unusual imaging characteristics with histologic correlation. - Fleege, M A; Miller, G M; Fletcher, G P; Fain, J S; Scheithauer, B W (American Journal of Neuroradiology, 1994)
PURPOSE To describe the spectrum of MR and CT findings in clinically symptomatic pineal cysts and to determine whether there are certain diagnostic imaging features that allow one to distinguish a benign pineal cyst from other neoplasms of the pineal region. METHODS MR and CT scans of 19 patients with clinically symptomatic pineal cysts were retrospectively reviewed. Age range was 15 to 46 years with a mean age of 28 years. There were five male and 14 female patients. RESULTS Presenting features included headache (15 patients), diplopia (four), nausea and vomiting (four), papilledema (four), seizure (three), Parinaud syndrome (two), ataxia (one), and hemiparesis (one). All cysts were resected or biopsied to provide histopathologic confirmation of the diagnosis. Preoperative diagnoses included pineal neoplasm (14 of 19), pineal cyst (3 of 19), and dermoid cyst (2 of 19). The lesions ranged from 0.8 to 3.0 cm, with a mean diameter of 1.6 cm. Three cysts showed fluid/fluid levels consistent with hemorrhage. Slightly less than half (9 of 19) had evidence of hydrocephalus. The MR signal changes were variable but typically demonstrated low signal on T1-weighted images and high signal on T2-weighted images. More than half (7 of 12) demonstrated enhancement with gadolinium. Calcification of the cyst wall was observed in only four of nine patients who had CT studies but identified histologically in all cases. CONCLUSION The MR appearance of benign pineal cysts is variable, ranging from that of an uncomplicated cystic mass to a mass associated with hemorrhage, enhancement, or hydrocephalus. This variability may make them indistinguishable from other pineal-region tumors.